When the Robot Meets the Turtle: A Gentle Introduction to Algorithms and Functions - Vidal Duarte, Elizabeth (2017)
Educators have long been trying to motivate students in their introductory programming courses. Games help students to practice formulas, facts and processes, motivating learning by adding fun. This work describes our experience in the use of Lightbot and the graphic library Turtle to introduce students to the concepts of algorithm and function. This approach has been implemented in two Universities in Arequipa. We present the assignments used in the first and second session of CS1. Our experience has shown us that students get a clear understanding of algorithm and functions that are later implemented with Python (Universidad La Salle) and Java (Universidad Nacional de San Agustin). We believe that the visual nature of games and the graphical component to teaching anything is more effective for students. Results were measured by students' perception in 2016.